Low Serum Interleukin-10 Is an Independent Predictive Factor for the Risk of Second Event in Clinically Isolated Syndromes - Wei, Yuzhen; Chang, Haoxiao; Feng, Hao; Li, Xindi; Zhang, Xinghu; Yin, Linlin (Frontiers in Neurology, 2019)
Objective: To evaluated the prognostic ability of several serum cytokines in clinically isolated syndrome (CIS) patients regarding second events and conversion to multiple sclerosis (MS) or neuromyelitis optica spectrum disorder (NMOSD). Methods: We enrolled 69 CIS patients whose serum samples were collected during the acute phase of the first onset before immunotherapy. Fifteen other non-inflammatory neurological disorder (OND) patients were also included. The serum levels of interleukin (IL)-2, IL-4, IL-6, IL-10, IL-13, IL-17A, IL-21, IL-23, interferon-γ (IFN-γ) and transforming growth factor beta 1 (TGF-β1) were measured using the human cytokine multiplex assay or ELISA. Patients were seen every 3 to 6 months. Unscheduled visits occur in case of exacerbations. Clinical measures of disease progression were recorded. Results: 20 CIS cases had second events during follow-up at a mean time of 15.3 ± 9.9 months. Serum IL-10 levels were significantly lower in CIS patients who relapsed compared to patients who did not. Low serum IL-10 levels were associated with higher risk and shorter times to second events. In clinical correlations, a significantly higher CSF white blood cells count, number of T2 lesions, and gadolinium-enhancing (Gd+) lesions in baseline MRI were found in the low serum IL-10 level group. Of the 20 relapsed cases, 7 converted to MS, and 8 converted to NMOSD. No significant diﬀerences were found in any cytokine levels between these patients at first onset. Conclusions: These findings support using serum IL-10 as a biomarker associated with the risk of relapse and the time to second events in patients with CIS. However, serum cytokine levels can not differentiate between the conversion from CIS to MS or NMOSD.